Chemical diversity and biological activities of specialized metabolites from the genus Chaetomium: 2013–2022. (June 2023) - Rao, Qian-Ru; Rao, Jian-Bo; Zhao, Min
Abstract: Chaetomium (Chaetomiaceae), a large fungal genus consisting of at least 400 species, has been acknowledged as a promising resource for the exploration of novel compounds with potential bioactivities. Over the past decades, emerging chemical and biological investigations have suggested the structural diversity and extensive potent bioactivity of the specialized metabolites in the Chaetomium species. To date, over 500 compounds with diverse chemical types have been isolated and identified from this genus, including azaphilones, cytochalasans, pyrones, alkaloids, diketopiperazines, anthraquinones, polyketides, and steroids. Biological research has indicated that these compounds possess a broad range of bioactivities, including antitumor, anti-inflammatory, antimicrobial, antioxidant, enzyme inhibitory, phytotoxic, and plant growth inhibitory activities. This paper summarizes current knowledge referring to the chemical structure, biological activity, and pharmacologic potency of the specialized metabolites in the Chaetomium species from 2013 to 2022, which might provide insights for the exploration and utilization of bioactive compounds in this genus both in the scientific field and pharmaceutical industry. Graphical abstract: Image 1 Highlights: Overview of specialized metabolites isolated from the genus Chaetomium. A total of 182 specialized metabolites were summarized. The structures and isolations of these compounds were described. The biological activities of the isolated compounds were summarized. Benefit for new drug development of the genus Chaetomium.